Faktor-Faktor yang Berhubungan dengan Kasus Filariasis di Indonesia : Sistematik Review - Inggita Raiesa Rahmi; Dwi Sutiningsih; Retno Hestiningsih; Lintang Dian Saraswati (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: Good knowledge of what factors are associated with filariasis cases, can determine effective control and prevention. Because each region has different risk factors.The purpose of this study was to determine what factors are associated with cases of filariasis in Indonesia.Methods: This study used systematic review method using database search from Google Scholar, Sciencedirect, Researhgate, Scopus, PubMed and Grey Literature. This study used search keyword “Factor risk” with boolean operators AND “Filariasis” OR “Elephantiasis”. The quality of the article assessed using the guideline from Joanna Briggs Institute Critical Appraisal Checklist. The articles that met the inclusion criteria and have medium to high quality were analyzed. .Result: the result showed that 6 articles with Cross-sectional study design and 24 articles with Case control study design were included in the analysis. The results of the quality assessment of the articles showed that most of the articles were moderate to good quality. Factors related to filariasis are Going at night (19%), mosquito repellent (15%), mosquito net (19%), wear closed clothing (9%), wire-net use (16%), bushes (4%), swamps (6%), rice fields (2%), cattle pens (6%) and puddles (4%)Conclusion: factors related to filariasis are Going at night, mosquito repellent, mosquito net, wear closed clothing, wire-net use, bushes, swamps, rice fields, cattle pens, puddles. To control cases of filariasis must consider these factors.